PERBANDINGAN ECONOMIC VALUE ADDED (EVA) DAN RASIO PROFITABILITAS DALAM PENGUKURAN KINERJA KEUANGAN PT TELKOM INDONESIA TBK PERIODE 2017-2019 - Tambunan, Aprinalda F.; Ilat, Ventje; Pangerapan, Sonny (GOING CONCERN : JURNAL RISET AKUNTANSI, 2021)
Financial performance measurement is the process of recording and assessing the company’s achievements in managing finances according to the predetermined goals and standards. This study aims to determine and compare the financial performance of PT Telkom Indonesia Tbk for the 2017-2019 period measured by the economic value added method and profitability ratio. The research method used descriptive qualitative. The method of data analysis used descriptive analysis, done by collecting data, analyzed and then drawn a conclusion. The result showed that the financial performance of PT Telkom Indonesia Tbk in the period 2017-2018 measured by the economic value added method are not good because EVA has negative value (EVA < 0), but in the period 2019 the company’s financial performance is in good condition because EVA has positive value (EVA > 0), meanwhile using the overall profitability ratio is quite good, because the percentage of the profitability ratio is positive which means that the company is still able to generate profit. The comparison of the two methods shows that there are differences in the measurement of financial performance because the economic value added takes into account the cost of capital, while the profitability ratio only focuses on assesing the company’s ability to create profits without taking into account the cost of capital.